Association of Pulmonary Hypertension with Mortality in Incident Peritoneal Dialysis Patients. Issue 5 (September 2015) - Xu, Qingdong; Xiong, Liping; Fan, Li; Xu, Fenghua; Yang, Yan; Li, Huiyan; Peng, Xuan; Cao, Shirong; Zheng, Zhihua; Yang, Xiao; Yu, Xueqing; Mao, Haiping
Background: The prognostic value of pulmonary hypertension at the start of peritoneal dialysis (PD) in patient survival is unclear. Methods: We conducted a retrospective study of incident patients who initiated PD therapy from January 2007 to December 2011, and followed up through June 2013. Pulmonary hypertension was defined as an estimated systolic pulmonary artery pressure (PAP) of ≥ 35 mm Hg using echocardiography. Clinical parameters and laboratory findings were compared between patients with and without pulmonary hypertension and a logistic regression model was elaborated. Patient outcomes (all-cause and cardiovascular mortality) were recorded during follow-up. Survival curves were constructed by the Kaplan-Meier method, and the influences of pulmonary hypertension on outcomes were analyzed by Cox regression models. Results: Pulmonary hypertension was prevalent in 99 (16.0%) of the 618 patients studied. The independent risk factors for pulmonary hypertension were female (odds ratio [OR] = 2.12; 95% confidence interval [CI]: 1.29 – 3.46), left atrial diameter (OR = 1.15; 95% CI: 1.10 – 1.20), left ventricular ejection fraction (OR = 0.97; 95% CI: 0.95 – 0.99), and serum sodium (OR = 0.94; 95% CI: 0.89 – 0.99). Over a median follow-up of 29.4 months, 93 patients (15.0%) died, 59.1% of them due to cardiovascular disease. Kaplan-Meier survival analysis showed that patients with pulmonary hypertension had worse overall rates of survival and cardiovascular death-free survival than those without pulmonary hypertension. After multivariate adjustment, pulmonary hypertension was independently associated with increased risk for both all-cause and cardiovascular mortality, with hazard ratios (HRs) of 2.10 (95% CI: 1.35 – 3.27) and 2.60 (95% CI: 1.48 – 4.56), respectively. Conclusions: The prevalence of pulmonary hypertension at the start of PD was common and associated with increased risk of both all-cause and cardiovascular mortality in incident PD patients.